Follow Your Nose: Extended Arm Reach After Pinocchio Illusion in Virtual Reality - Berger, Christopher C.; Lin, Baihan; Lenggenhager, Bigna; Lanier, Jaron; Gonzalez-Franco, Mar (Frontiers in Virtual Reality, 2022)
In this study, we recreate the Pinocchio Illusion—a bodily illusion whereby the perceived length of one’s nose is extended—in Virtual Reality. Participants (n = 38) self-administered tapping on the tip of the nose of a virtual avatar seen from the first-person perspective (using a hand-held controller) while the nose of the avatar slowly grew with each tap. The stimulating virtual arm and the virtual nose were linked such that while the nose grew the arm extended, and then also grew up to 50%. This produced an extension of the perceived reach of the stimulating arm, and an outward drift in the participants’ real arm. A positive correlation between the extent of the outward drift of the participants’ arm and the perceived reachability of distal objects was observed. These results were found both with synchronous tactile stimulation on the participants’ real nose, and without, but not for control conditions in which the visuomotor synchrony or body schema were violated. These findings open new avenues for hand grasp interactions with virtual objects out of arm’s-reach in immersive setups and are discussed in the context of theories of body ownership, body schema, and touch perception.